2021
DOI: 10.1093/eurjpc/zwab061.182
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide cross-sectional epidemiological study of cardiovascular risk factors as a tool for management of primary and secondary prevention in Latvia

Abstract: Funding Acknowledgements Type of funding sources: Public grant(s) – EU funding. Main funding source(s): EUROPEAN SOCIAL FUND MINISTRY OF HEALTH, LATVIA Background. An increasing prevalence (PREV.) of noncomunicable diseases is a major public health concern  in Latvia. Regular nationwide epidemiological studies present an opportunity to estimate the dinamics of PREV of health risk factors (RF) and thus assist in planning resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on World Health Organization (WHO) cardiovascular mortality rates, Latvia is in a very high-risk region, and nearly every female patient aged more than 40 years and with non-high-density lipoprotein (non-HDL) cholesterol >3 mmol/L has a high or very high 10-year risk of cardiovascular events as calculated by SCORE-2 or SCORE2-OP risk stratification charts [1]. A population-based cross-sectional study of cardiovascular risk factors (CVRs) in Latvia from 2009 to 2019 also revealed that women aged 25-74 years are in a very high CVR group: 61% of women have dyslipidemia, more than 33% have Medicina 2022, 58, 1139 2 of 12 arterial hypertension (AH), and 28% are overweight [2]. The data indicate the necessity for focused diagnostics and the early detection of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Based on World Health Organization (WHO) cardiovascular mortality rates, Latvia is in a very high-risk region, and nearly every female patient aged more than 40 years and with non-high-density lipoprotein (non-HDL) cholesterol >3 mmol/L has a high or very high 10-year risk of cardiovascular events as calculated by SCORE-2 or SCORE2-OP risk stratification charts [1]. A population-based cross-sectional study of cardiovascular risk factors (CVRs) in Latvia from 2009 to 2019 also revealed that women aged 25-74 years are in a very high CVR group: 61% of women have dyslipidemia, more than 33% have Medicina 2022, 58, 1139 2 of 12 arterial hypertension (AH), and 28% are overweight [2]. The data indicate the necessity for focused diagnostics and the early detection of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%